NEW PRIMERS FOR DETECTION OF Leishmania infantum USING POLYMERASE CHAIN REACTION - GUALDA, Kézia Peres; MARCUSSI, Lílian Mathias; NEITZKE-ABREU, Herintha Coeto; ARISTIDES, Sandra Mara Alessi; LONARDONI, Maria Valdrinez Campana; CARDOSO, Rosilene Fressatti; SILVEIRA, Thaís Gomes Verzignassi (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Leishmania infantum causes visceral leishmaniasis (VL) in the New World. The diagnosis of VL is confirmed by parasitological and serological tests, which are not always sensitive or specific. Our aim was to design new primers to perform a Polymerase Chain Reaction (PCR) for detecting L. infantum. Sequences of the minicircle kinetoplast DNA (kDNA) were obtained from GenBank, and the FLC2/RLC2 primers were designed. Samples of DNA from L. infantum, Leishmania amazonensis, Leishmania braziliensis, Leishmania guyanensis, Leishmania naiffi, Leishmania lainsoni, Leishmania panamensis, Leishmania major and Trypanosoma cruzi were used to standardize the PCR. PCR with FLC2/RLC2 primers amplified a fragment of 230 bp and the detection limit was 0.2 fg of L. infantum DNA. Of the parasite species assayed, only L. infantum DNA was amplified. After sequencing, the fragment was aligned to GenBank sequences, and showed (99%) homology with L. infantum. In the analysis of blood samples and lesion biopsy from a dog clinically suspected to have VL, the PCR detected DNA from L. infantum. In biopsy lesions from humans and dogs with cutaneous leishmaniasis, the PCR was negative. The PCR with FLC2/RLC2 primers showed high sensitivity and specificity, and constitutes a promising technique for the diagnosis of VL.